Cross-platform desktop application development, Electron, Node, NW.js, and React : build desktop applications with web technologies - Sheiko, Dmitry (Birmingham, UK : Packt Publishing, 2017)
Build powerful cross-platform desktop applications with web technologies such as Node, NW. JS, Electron, and React About This Book Build different cross-platform HTML5 desktop applications right from planning, designing, and deployment to enhancement, testing, and delivery Forget the pain of cross-platform compatibility and build efficient apps that can be easily deployed on different platforms. Build simple to advanced HTML5 desktop apps, by integrating them with other popular frameworks and libraries such as Electron, Node. JS, Nw.js, React, Redux, and TypeScript Who This Book Is For This book has been written for developers interested in creating desktop applications with HTML5. The first part requires essential web-master skills (HTML, CSS, and JavaScript). The second demands minimal experience with React. And finally for the third it would be helpful to have a basic knowledge of React, Redux, and TypeScript. What You Will Learn Plan, design, and develop different cross-platform desktop apps Application architecture with React and local state Application architecture with React and Redux store Code design with TypeScript interfaces and specialized types CSS and component libraries such as Photonkit, Material UI, and React MDL HTML5 APIs such as desktop notifications, WebSockets, WebRTC, and others Desktop environment integration APIs of NW.js and Electron Package and distribute for NW. JS and Electron In Detail Building and maintaining cross-platform desktop applications with native languages isn't a trivial task. Since it's hard to simulate on a foreign platform, packaging and distribution can be quite platform-specific and testing cross-platform apps is pretty complicated. In such scenarios, web technologies such as HTML5 and JavaScript can be your lifesaver. HTML5 desktop applications can be distributed across different platforms (Window, MacOS, and Linux) without any modifications to the code. The book starts with a walk-through on building a simple file explorer from scratch powered by NW. JS. So you will practice the most exciting features of bleeding edge CSS and JavaScript. In addition you will learn to use the desktop environment integration API, source code protection, packaging, and auto-updating with NW. JS. As the second application you will build a chat-system example implemented with Electron and React. While developing the chat app, you will get Photonkit. Next, you will create a screen capturer with NW. JS, React, and Redux. Fina ...
Packaging and distribution -- Deployment and updates -- Summary -- Chapter 5: Creating a Screen Capturer with NW.js, React, and Redux -- Planning, Design, and Development -- Application blueprint -- Setting up the development environment -- Static prototype -- Comprehending redux -- Introducing the application state -- Summary -- Chapter 6: Creating a Screen Capturer with NW.js: Enhancement, Tooling, and Testing -- Tooling Redux -- Redux DevTools -- Unit-testing Redux -- Testing action creator -- Testing reducers -- Taking a screenshot -- Recording a screencast -- Taking advantage of the system tray -- Registering global keyboard shortcuts -- Summary -- Chapter 7: Creating RSS Aggregator with Electron, TypeScript , React, and Redux: Planning, Design, and Development -- Application blueprint -- Welcome to TypeScript -- Setting up the development environment for TypeScript -- Basic types -- Array, plain objects, and indexable types -- Function type -- Class type -- Abstract classes -- Enum type -- Union and intersection types -- Generic type -- Global libraries -- Creating static prototype -- Setting up the development environment for the application -- React-MDL -- Creating the index.html -- Creating the container component -- Creating the TitleBar component -- Creating the Menu component -- Creating the feed component -- Adding custom styles with SASS -- Summary -- Chapter 8: Creating RSS Aggregator with Electron, TypeScript, React, and Redux: Development -- Creating a service to fetch RSS -- Creating a service to manage feed menu -- Actions and Reducers -- Connecting to the store -- Consuming store from the components -- Creating router service -- Summary -- Index.
Online resource; title from title page (Safari, viewed August 15, 2017).
Added to collection customer.56279.3
Keywords: Electron (Application development framework); Node.js.; Node.js; Application software -- Development -- Computer programs; Logiciels d'application -- Développement -- Logiciels; COMPUTERS -- Internet -- Application Development; Application software -- Development -- Computer programs